Rubber as well as preparation method and application thereof

By using a new rubber containing fluoro-rubber, ethylene propylene ternary rubber and modified nanotitanium dioxide in the rubber roller for steel plates, the problem of insufficient pressure resistance and high-temperature aging resistance of existing rubber rollers when used in high-pressure and high-temperature environments is solved, and the service life is significantly extended.

CN119842173AActive Publication Date: 2025-04-18CHUNFENG YINXING RUBBER ROLLER CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510345250.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-18
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

When existing rubber rollers for steel plates are used under high pressure and high temperature environments, the rubber layer is prone to deformation, depression, rupture and poor high-temperature aging resistance, resulting in a shortening of service life.

Method used

A new type of rubber is adopted, whose components include a mixture of fluoro-rubber, ethylene propylene ternary rubber and chlorosulfonated polyethylene rubber, and modified nanotitanium dioxide, modified carbon fiber, vulcanizing agent, accelerator, silane coupling agent and anti-aging agent. Through the synergistic effect of these components, the rubber's high-temperature aging resistance and pressure resistance are improved.

Benefits of technology

It significantly improves the high-temperature aging and pressure resistance of rubber, extends its service life, and avoids the problems of deformation, depression and cracking of rubber under high temperature and high pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and particularly discloses rubber as well as a preparation method and application thereof. The rubber provided by the invention is prepared from 50 to 60 parts of matrix rubber, 4 to 6 parts of modified nano titanium dioxide, 6 to 10 parts of modified carbon fiber, 1 to 2 parts of vulcanizing agent, 0.7 to 1.0 part of accelerant, 8 to 10 parts of silane coupling agent and 1 to 3 parts of anti-aging agent. According to the rubber provided by the invention, the mixture of the fluororubber, the ethylene propylene diene monomer and the chlorosulfonated polyethylene rubber is used as matrix rubber, and the modified nano titanium dioxide, the modified carbon fibers, the vulcanizing agent, the accelerant, the silane coupling agent and the anti-aging agent are added at the same time; the prepared rubber has excellent high-temperature aging resistance and pressure resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a rubber and a preparation method and application thereof. Background Art

[0002] In the production process of modern steel industry, rubber rollers for steel plates play a vital role. They are widely used in many key links such as steel plate transportation, rolling and surface treatment.

[0003] In the steel plate rolling process, the rubber roller needs to withstand huge rolling pressure. However, the existing rubber rollers for steel plates have significant defects in pressure resistance. Traditional rubber rollers are prone to deformation, dents, and even cracks in the rubber layer under long-term high-pressure working environments. In addition, in some steel plate production scenarios, a high working temperature environment is involved. For example, in the subsequent processing of hot-rolled steel plates, the temperature around the rubber roller can often reach above 180°C. The existing rubber rollers for steel plates have poor high-temperature aging resistance. After long-term use in a high-temperature environment, the rubber material will age and harden, causing the surface of the rubber roller to lose elasticity and reduce friction, thereby affecting the transportation and processing of the steel plate. The aged rubber rollers are also prone to problems such as degumming, which greatly shortens the overall service life of the rubber rollers, greatly limiting the efficient and stable operation of the steel plate production process. In summary, the development of a rubber roller with excellent pressure resistance and high-temperature aging resistance has become an important technical problem that needs to be solved in the current steel industry. Summary of the invention

[0004] Aiming at the problem that the existing rubber has poor high temperature resistance and pressure resistance, the present invention provides a rubber and a preparation method and application thereof.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is: The present invention provides a rubber, comprising the following raw material components in parts by weight: 50-60 parts of base rubber, 4-6 parts of modified nano titanium dioxide, 6-10 parts of modified carbon fiber, 1-2 parts of vulcanizing agent, 0.7-1.0 parts of accelerator, 8-10 parts of silane coupling agent and 1-3 parts of antioxidant; The base rubber is a mixture of fluororubber, EPDM rubber and chlorosulfonated polyethylene rubber; The modified nano titanium dioxide is nano titanium dioxide modified by polydopamine and polyethylene glycol; The modified carbon fiber is a carbon fiber calcined at high temperature.

[0006] Compared with the prior art, in the rubber provided by the present invention, the fluororubber has excellent high-temperature aging resistance, stable molecular structure, and can still maintain good physical and chemical properties at high temperatures. The use of fluororubber improves the high-temperature aging resistance and pressure resistance of the rubber to a certain extent; the addition of EPDM rubber can further improve the high-temperature aging resistance of the rubber, and its stable molecular structure also makes the EPDM rubber have excellent elasticity. Adding it to the rubber system can enable the rubber to play a buffering role under pressure conditions, reduce rubber stress concentration, and improve pressure resistance. In addition, the addition of EPDM rubber to the rubber system is also conducive to forming a uniform and stable structure with other base rubbers, thereby improving the service life of the rubber; the chlorosulfonyl group in the chlorosulfonated polyethylene rubber further enhances the thermal stability of the rubber, and it is cross-linked with the fluororubber and the EPDM rubber to form a network structure, which further stabilizes the overall structure of the rubber, thereby improving the pressure resistance of the rubber.

[0007] In the modified nano titanium dioxide provided by the present invention, polydopamine has thermal stability and can form a strong chemical bond or hydrogen bond with the active group on the molecular chain of the matrix rubber under high temperature environment, thereby limiting the excessive movement of the matrix rubber at high temperature, effectively improving the high temperature aging resistance of the rubber, and after the rubber is subjected to force, the polydopamine enhances the interface bonding force between the modified nano titanium dioxide and the matrix rubber, uniformly dispersing the pressure to other parts of the rubber matrix, preventing local pressure concentration from causing rupture, thereby improving the pressure resistance of the rubber; polyethylene glycol has certain fluidity and lubricity, and the nano titanium dioxide is modified by polyethylene glycol, so that the friction between the nano titanium dioxide and the molecular chain of the matrix rubber can be reduced, thereby ensuring the elasticity of the rubber at high temperature and improving the pressure resistance. At the same time, the nano titanium dioxide modified by polydopamine and polyethylene glycol can make the titanium dioxide uniformly distributed in the matrix rubber, and the flexible chain segment of polyethylene glycol can also assist the nano titanium dioxide to better disperse the pressure, thereby improving the pressure resistance of the rubber, and further improving the service life of the rubber under high pressure.

[0008] Carbon fibers calcined at high temperatures have a larger specific surface area and more active groups. Adding modified carbon fibers to the rubber system can improve the bonding strength between the carbon fibers and the matrix rubber. When subjected to stress, the stress can be effectively dispersed between the carbon fibers and the matrix rubber, avoiding problems such as rubber breakage caused by excessive stress concentration, thereby extending the service life of the rubber. Carbon fibers calcined at high temperatures have a stable structure under high temperature conditions and can limit the movement of the matrix rubber molecular chains at high temperatures, thereby significantly improving the high temperature aging resistance of the rubber.

[0009] In the present invention, the vulcanizing agent can promote the crosslinking between the base rubber molecules, the accelerator can accelerate the reaction rate between the vulcanizing agent and the base rubber, the silane coupling agent improves the crosslinking degree between the base rubbers by participating in the vulcanization reaction, and the silane coupling agent can also enhance the bonding force between the base rubber and other fillers, and the antioxidant can inhibit the aging of the rubber.

[0010] The rubber provided by the present invention uses a mixture of fluororubber, EPDM rubber and chlorosulfonated polyethylene rubber as a base rubber, and is simultaneously added with modified nano titanium dioxide, modified carbon fiber, a vulcanizing agent, an accelerator, a silane coupling agent and an antioxidant. The synergistic effect between the raw material components enables the prepared rubber to have both excellent high temperature aging resistance and pressure resistance.

[0011] The mass ratio of fluororubber, EPDM rubber and chlorosulfonated polyethylene rubber in the base rubber is 4:(2.5-3):(3-3.5).

[0012] The invention can make the rubber have high temperature aging resistance and pressure resistance at the same time by limiting the usage relationship between the three base rubbers.

[0013] The preparation method of the modified nano titanium dioxide comprises the following steps: a. Dispersing nano titanium dioxide in water to obtain a nano titanium dioxide dispersion; b. Adding dopamine to the nano titanium dioxide dispersion at a pH of 8 to 9, and keeping the temperature at 30° C. to 35° C. to obtain a polydopamine-modified nano titanium dioxide dispersion; c. Adding polyethylene glycol and toluenesulfonyl chloride into dichloromethane to obtain a polyethylene glycol mixed solution; d. Add the polyethylene glycol mixed solution into the polydopamine modified nano titanium dioxide dispersion, and keep the temperature at 50° C.-55° C. to obtain the modified nano titanium dioxide.

[0014] In the modified nano titanium dioxide preparation method provided by the present invention, under specific alkaline conditions, dopamine can self-polymerize on the surface of nano titanium dioxide to form polydopamine, which contains some rich amino and phenolic hydroxyl active sites, which are conducive to the subsequent grafting of polyethylene glycol; toluenesulfonyl chloride can activate the hydroxyl groups on polyethylene glycol, thereby making it easier to graft it onto polydopamine to form stable modified nano titanium dioxide. The preparation method provided by the present invention is simple, and the conditions during the preparation process are mild, and modified nano titanium dioxide with excellent performance can be efficiently prepared, laying a solid foundation for improving the comprehensive performance of rubber.

[0015] Preferably, in step a, the particle size of the nano titanium dioxide is 25nm-28nm.

[0016] Preferably, in step a, the concentration of the nano-titanium dioxide dispersion is 20 g / L-30 g / L.

[0017] Preferably, the mass ratio of the nano-titanium dioxide to dopamine is (7-8):1.

[0018] Preferably, in step b, the insulation time is 25h-30h.

[0019] Further preferably, in step b, stirring is also required during the heat preservation, and the stirring rate is 300rpm-400rpm.

[0020] Preferably, in step c, the polyethylene glycol is polyethylene glycol 4000.

[0021] Preferably, in step c, the molar ratio of polyethylene glycol to toluenesulfonyl chloride is 1:(1-2).

[0022] Preferably, in step c, the concentration of polyethylene glycol in the polyethylene glycol mixed solution is 0.5 mol / L-0.8 mol / L.

[0023] Preferably, the mass ratio of the nano-titanium dioxide to polyethylene glycol is 1:(0.6-0.7).

[0024] Preferably, in step d, the insulation time is 18h-24h.

[0025] Preferably, in step d, stirring is also required during the heat preservation.

[0026] Preferably, in step d, the mixture after the insulation is completed needs to be post-processed, which specifically includes the following: centrifugation, solid-liquid separation, washing, and drying to obtain the modified nano titanium dioxide.

[0027] Preferably, the high temperature calcination conditions are: temperature 380°C-390°C, time 40min-45min.

[0028] The present invention further limits the calcination conditions. The inventors have found through extensive research that the temperature and time of high-temperature calcination are extremely critical to the performance of carbon fiber. When the temperature is too high, the carbon fiber is over-oxidized, thereby reducing the strength of the carbon fiber; when the temperature is too low, the performance of the oxidized carbon fiber is unstable, and there are fewer surface active groups, which reduces the bonding strength with the matrix rubber.

[0029] The silane coupling agent is at least one of vinyl triethoxy silane and γ-glycidyloxypropyl trimethoxy silane.

[0030] The vulcanizing agent is at least one of dicumyl peroxide and 2,4-dichlorobenzoyl peroxide.

[0031] The accelerator is dibenzothiazyl disulfide.

[0032] The antioxidant is at least one of antioxidant MB and antioxidant AW.

[0033] The present invention provides a method for preparing the above-mentioned rubber, comprising the following steps: S1. Mixing the weighed base rubber, modified nano titanium dioxide and modified carbon fiber and kneading them at 90° C.-100° C. to obtain a base rubber mixture; S2, mixing the vulcanizing agent, accelerator, silane coupling agent, antioxidant and base rubber mixture at 110° C.-115° C. and kneading to obtain a primary rubber mixture; S3. vulcanizing the primary rubber mixture at 140° C.-145° C. to obtain rubber.

[0034] The rubber preparation method provided by the invention significantly improves the comprehensive performance of rubber products, has extremely high industrial application value, is easy to operate, and is suitable for factory production.

[0035] Preferably, in S1, the mixing time is 30 min-40 min.

[0036] Preferably, in S1, the mixing needs to be stirred at a rotation speed of 30 r / min-60 r / min.

[0037] Preferably, in S2, the mixing time is 15 min-20 min.

[0038] Preferably, in S2, the mixing needs to be stirred at a rotation speed of 30 r / min-60 r / min.

[0039] It should be further explained that, in S2, a debonding process is required after the mixing is completed.

[0040] Preferably, in S3, the vulcanization treatment time is 30 min-40 min.

[0041] The present invention provides application of the rubber or the rubber prepared by the rubber method in preparing a rubber roller for steel plates. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0043] In order to better illustrate the present invention, further examples are given below.

[0044] Example 1 This embodiment provides a rubber, comprising the following raw material components in parts by weight: 60 parts of base rubber, 4 parts of modified nano titanium dioxide, 10 parts of modified carbon fiber, 1 part of diisopropylbenzene peroxide, 1 part of dibenzothiazole disulfide, 8 parts of vinyl triethoxysilane, and 3 parts of antioxidant MB; The base rubber is a mixture of fluororubber, EPDM rubber and chlorosulfonated polyethylene rubber in a mass ratio of 4:2.5:3; The preparation method of modified nano titanium dioxide comprises the following steps: a. Disperse 70 g of nano titanium dioxide with a particle size of 25 nm in water to obtain a nano titanium dioxide dispersion with a concentration of 20 g / L; b. At a pH of 9, 10 g of dopamine was added to the nano-titanium dioxide dispersion, and the mixture was kept at 30° C. for 25 h. During the keeping, the mixture was stirred at a rate of 300 rpm to obtain a polydopamine-modified nano-titanium dioxide dispersion; c. Add 42 g (0.0105 mol) of polyethylene glycol 4000 and 2 g (0.0105 mol) of toluenesulfonyl chloride into dichloromethane to obtain a polyethylene glycol mixed solution with a polyethylene glycol 4000 concentration of 0.5 mol / L; d. adding the polyethylene glycol mixed solution to the polydopamine modified nano titanium dioxide dispersion, keeping warm at 55° C. for 18 h, centrifuging, solid-liquid separation, washing, and drying to obtain modified nano titanium dioxide; The treatment conditions of the modified carbon fibers were as follows: calcined at 380°C for 45 min.

[0045] The method for preparing the rubber provided in this embodiment comprises the following steps: S1. At 100° C., the weighed base rubber, modified nano titanium dioxide and modified carbon fiber are mixed and kneaded for 30 minutes. Stirring is required during kneading. The speed is 30 r / min to obtain a base rubber mixture. S2. At 110° C., dicumyl peroxide, dibenzothiazole disulfide, vinyl triethoxysilane, antioxidant MB and the base rubber mixture were mixed and kneaded for 15 minutes. Stirring was required during the mixing, and the speed was 30 r / min to obtain a primary rubber mixture; S3. vulcanizing the primary rubber mixture at 140° C. for 30 minutes to obtain rubber.

[0046] Example 2 This embodiment provides a rubber, comprising the following raw material components in parts by weight: 50 parts of base rubber, 6 parts of modified nano titanium dioxide, 6 parts of modified carbon fiber, 2 parts of 2,4-dichlorobenzoyl peroxide, 0.7 parts of dibenzothiazole disulfide, 10 parts of γ-glycidyloxypropyltrimethoxysilane, and 1 part of antioxidant AW; The base rubber is a mixture of fluororubber, EPDM rubber and chlorosulfonated polyethylene rubber in a mass ratio of 4:3:3.5; The preparation method of modified nano titanium dioxide comprises the following steps: a. Disperse 80 g of nano titanium dioxide with a particle size of 28 nm in water to obtain a nano titanium dioxide dispersion with a concentration of 30 g / L; b. At a pH of 8, 10 g of dopamine was added to the nano-titanium dioxide dispersion, and the mixture was kept at 35° C. for 30 h. During the keeping, the mixture was stirred at a rate of 400 rpm to obtain a polydopamine-modified nano-titanium dioxide dispersion; c. Add 56 g (0.014 mol) of polyethylene glycol 4000 and 5.34 g (0.028 mol) of toluenesulfonyl chloride into dichloromethane to obtain a polyethylene glycol mixed solution with a polyethylene glycol 4000 concentration of 0.8 mol / L; d. adding the polyethylene glycol mixed solution to the polydopamine modified nano titanium dioxide dispersion, keeping warm at 50° C. for 24 h, centrifuging, solid-liquid separation, washing, and drying to obtain modified nano titanium dioxide; The treatment conditions of the modified carbon fibers were as follows: calcined at 390°C for 40 min.

[0047] The method for preparing the rubber provided in this embodiment comprises the following steps: S1. At 90° C., the weighed base rubber, modified nano titanium dioxide and modified carbon fiber were mixed and kneaded for 40 minutes. Stirring was required during the kneading, and the speed was 60 r / min to obtain a base rubber mixture; S2. At 115° C., 2,4-dichlorobenzoyl peroxide, dibenzothiazole disulfide, γ-glycidyloxypropyltrimethoxysilane, antioxidant AW and base rubber mixture were mixed and kneaded for 20 minutes. Stirring was required during kneading, and the speed was 60 r / min to obtain a primary rubber mixture; S3. vulcanizing the primary rubber mixture at 145° C. for 40 minutes to obtain rubber.

[0048] Example 3 This embodiment provides a rubber, comprising the following raw material components in parts by weight: 55 parts of base rubber, 5 parts of modified nano titanium dioxide, 8 parts of modified carbon fiber, 1.5 parts of 2,4-dichlorobenzoyl peroxide, 0.8 parts of dibenzothiazole disulfide, 9 parts of γ-glycidyloxypropyltrimethoxysilane, and 2 parts of antioxidant AW; The base rubber is a mixture of fluororubber, EPDM rubber and chlorosulfonated polyethylene rubber in a mass ratio of 4:2.8:3.2; The preparation method of modified nano titanium dioxide comprises the following steps: a. Disperse 75 g of nano titanium dioxide with a particle size of 26 nm in water to obtain a nano titanium dioxide dispersion with a concentration of 25 g / L; b. At a pH of 8.5, 10 g of dopamine was added to the nano-titanium dioxide dispersion, and the mixture was kept at 32° C. for 28 h. During the keeping, the mixture was stirred at a rate of 350 rpm to obtain a polydopamine-modified nano-titanium dioxide dispersion. c. Add 48.75 g (0.012 mol) of polyethylene glycol 4000 and 3.43 g (0.018 mol) of toluenesulfonyl chloride into dichloromethane to obtain a polyethylene glycol mixed solution with a polyethylene glycol 4000 concentration of 0.6 mol / L; d. adding the polyethylene glycol mixed solution to the polydopamine modified nano titanium dioxide dispersion, keeping warm at 53° C. for 20 h, centrifuging, solid-liquid separation, washing, and drying to obtain modified nano titanium dioxide; The treatment conditions of the modified carbon fibers were as follows: calcination at 385°C for 42 min.

[0049] The method for preparing the rubber provided in this embodiment comprises the following steps: S1. At 95° C., the weighed base rubber, modified nano titanium dioxide and modified carbon fiber were mixed and kneaded for 35 minutes. Stirring was required during the kneading, and the speed was 40 r / min to obtain a base rubber mixture; S2. At 112° C., 2,4-dichlorobenzoyl peroxide, dibenzothiazole disulfide, γ-glycidyloxypropyltrimethoxysilane, antioxidant AW and base rubber mixture were mixed and kneaded for 18 minutes. Stirring was required during kneading, and the speed was 40 r / min to obtain a primary rubber mixture; S3. vulcanizing the primary rubber mixture at 143° C. for 35 minutes to obtain rubber.

[0050] Comparative Example 1 This comparative example provides a rubber, which is different from Example 1 in that the EPDM rubber is replaced by an equal amount of fluororubber, and other operations are the same as Example 1.

[0051] Comparative Example 2 This comparative example provides a rubber, which is different from Example 1 in that the chlorosulfonated polyethylene rubber is replaced by an equal amount of fluororubber, and other operations are the same as Example 1.

[0052] Comparative Example 3 This comparative example provides a rubber, which is different from Example 1 in that the chlorosulfonated polyethylene rubber is replaced by an equal amount of hydrogenated nitrile rubber, and other operations are the same as Example 1.

[0053] Comparative Example 4 This comparative example provides a rubber, which is different from Example 1 in that the modified nano titanium dioxide is nano titanium dioxide modified with polydopamine, and the preparation method of the modified nano titanium dioxide comprises the following steps: a. Disperse 70 g of nano titanium dioxide with a particle size of 25 nm in water to obtain a nano titanium dioxide dispersion with a concentration of 20 g / L; b. At a pH of 9, add 10 g of dopamine to the nano-titanium dioxide dispersion, keep it warm at 30°C for 25 hours, stir it at a rate of 300 rpm, centrifuge it, separate the solid from the liquid, wash it, and dry it to obtain modified nano-titanium dioxide.

[0054] The other operations are the same as those in Example 1.

[0055] Comparative Example 5 This comparative example provides a rubber, which is different from Example 1 in that the modified nano titanium dioxide is polyethylene glycol-modified nano titanium dioxide, and the preparation method of the modified nano titanium dioxide comprises the following steps: a. Disperse 70 g of nano titanium dioxide with a particle size of 25 nm in water to obtain a nano titanium dioxide dispersion with a concentration of 20 g / L; b. Add 42 g (0.0105 mol) of polyethylene glycol 4000 and 2 g (0.0105 mol) of toluenesulfonyl chloride into dichloromethane to obtain a polyethylene glycol mixed solution with a polyethylene glycol 4000 concentration of 0.5 mol / L; c. adding the polyethylene glycol mixed solution to the nano-titanium dioxide dispersion, keeping warm at 55° C. for 18 h, centrifuging, separating the solid from the liquid, washing, and drying to obtain modified nano-titanium dioxide; The other operations are the same as those in Example 1.

[0056] Comparative Example 6 This comparative example provides a rubber. Compared with Example 1, the difference is that polyethylene glycol is replaced by an equal amount of hydroxypropyl methylcellulose, and the other operations are the same as Example 1.

[0057] Comparative Example 7 This comparative example provides a rubber. Compared with Example 1, the difference is that the modified carbon fiber is replaced by an equal amount of carbon fiber, the modification method of high-temperature calcination is not used, and the other operations are the same as Example 1.

[0058] The line pressure and high temperature aging resistance of the rubber prepared in Examples 1-3 of the present invention and Comparative Examples 1-7 were tested, and the specific testing methods are as follows: Among them, the high temperature aging performance test refers to GB / T3512-2014 vulcanized rubber or thermoplastic rubber hot air accelerated aging and heat resistance test; The line pressure of rubber is tested using a caster life tester provided by Zhongshan Bangteng Technology Development Co., Ltd. The specific parameters are: total wheel stroke 20,000m, time 120min, test speed 6km / h, test loads of 400kg, 500kg and 600kg respectively, contact length 8cm. If the tester has the function of automatically identifying product damage, when the polyurethane wheel is damaged, such as wheel body rupture, degumming, severe wear, etc., the tester will automatically stop; where, line pressure (kg / cm) = load / contact length.

[0059] The specific test results are shown in Table 1: Table 1 Test results

[0060] It can be seen from Table 1 of the present invention that the rubber prepared by the components and preparation method provided by the present invention has excellent high temperature aging resistance and pressure resistance. After being treated at a high temperature of 300°C for 72 hours, the change in tensile strength is less than 4.2%, and the change in elongation at break is less than 8.1%. By testing the line pressure under certain load conditions, the line pressure can reach 100kg / mm ​​without damage. It can be seen from Comparative Examples 1-7 that whether replacing the base resin of the present invention, changing the modification method of nano titanium dioxide in the present invention, or replacing the conditions of Example 1 with conventional carbon fiber, the heat aging and line pressure test values ​​of the rubber prepared in Comparative Examples 1-7 are lower than the test data provided in Examples 1-3 of the present invention.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A rubber, characterized in that: The invention comprises the following raw material components in parts by weight: 50-60 parts of base rubber, 4-6 parts of modified nano titanium dioxide, 6-10 parts of modified carbon fiber, 1-2 parts of vulcanizing agent, 0.7-1.0 parts of accelerator, 8-10 parts of silane coupling agent and 1-3 parts of antioxidant; The base rubber is a mixture of fluororubber, EPDM rubber and chlorosulfonated polyethylene rubber; The modified nano titanium dioxide is nano titanium dioxide modified by polydopamine and polyethylene glycol; The modified carbon fiber is a carbon fiber calcined at high temperature.

2. The rubber according to claim 1, characterized in that The mass ratio of fluororubber, EPDM rubber and chlorosulfonated polyethylene rubber in the base rubber is 4:(2.5-3):(3-3.5).

3. The rubber according to claim 1, characterized in that The preparation method of the modified nano titanium dioxide comprises the following steps: a. Dispersing nano titanium dioxide in water to obtain a nano titanium dioxide dispersion; b. Adding dopamine to the nano titanium dioxide dispersion at a pH of 8 to 9, and keeping the temperature at 30° C. to 35° C. to obtain a polydopamine-modified nano titanium dioxide dispersion; c. Adding polyethylene glycol and toluenesulfonyl chloride into dichloromethane to obtain a polyethylene glycol mixed solution; d. Add the polyethylene glycol mixed solution into the polydopamine modified nano titanium dioxide dispersion, and keep the temperature at 50° C.-55° C. to obtain the modified nano titanium dioxide.

4. The rubber according to claim 3, characterized in that In step a, the particle size of the nano titanium dioxide is 25nm-28nm; and / or In step a, the concentration of the nano titanium dioxide dispersion is 20 g / L-30 g / L; and / or The mass ratio of the nano titanium dioxide to dopamine is (7-8):

1.

5. The rubber according to claim 3, characterized in that In step b, the insulation time is 25h-30h; and / or In step c, the polyethylene glycol is polyethylene glycol 4000.

6. The rubber according to claim 3, characterized in that In step c, the molar ratio of polyethylene glycol to toluenesulfonyl chloride is 1:(1-2); and / or In step c, the concentration of polyethylene glycol in the polyethylene glycol mixed solution is 0.5 mol / L-0.8 mol / L; and / or The mass ratio of the nano titanium dioxide to the polyethylene glycol is 1:(0.6-0.7); and / or In step d, the insulation time is 18h-24h.

7. The rubber according to claim 3, characterized in that The high temperature calcination conditions are: temperature 380°C-390°C, time 40min-45min.

8. The rubber according to claim 1, characterized in that The silane coupling agent is at least one of vinyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane; and / or The vulcanizing agent is at least one of dicumyl peroxide and 2,4-dichlorobenzoyl peroxide.

9. A method for preparing the rubber according to any one of claims 1 to 8, characterized in that: The steps include: S1. Mixing the weighed base rubber, modified nano titanium dioxide and modified carbon fiber and kneading them at 90° C.-100° C. to obtain a base rubber mixture; S2, mixing the vulcanizing agent, accelerator, silane coupling agent, antioxidant and base rubber mixture at 110° C.-115° C. and kneading to obtain a primary rubber mixture; S3. vulcanizing the primary rubber mixture at 140° C.-145° C. to obtain rubber.

10. Use of the rubber according to any one of claims 1 to 8 or the rubber prepared by the method for preparing the rubber according to claim 9 in preparing a rubber roller for steel plates.

Citation Information

Patent Citations

  • Automotive high-temperature-resistant rubber

    CN105733040A

  • Fluororubber crosslinking composition and molded article

    CN118139924A

  • Rubber composition and vulcanized rubber product

    US4942202A